Code-switching, code-mixing and code-conflicting in abeni by Tunde Kelani (2020)
Code-mixing is referred to as the mixing of two or more languages or language varieties in speech while code-switching is the practice of alternating between two or more languages or varieties of language in conversation. Previous works have examined code-switching and code-mixing with little attention paid to code-switching and codemixing of Yoruba and French in the film titled Abeni (Part 1 & 2), a Yoruba-French home video produced and directed by Tunde Kelani of Mainframe Productions in Nigeria in 2006. This article, therefore examines code-Switching, code-Mixing and code-conflicting in Abeni (Part 1 & 2) with a view to establishing the codeswitching and code-mixing in French and Yoruba languages. This movie is worth studying not just because it is a Yoruba–Beninese film but it also has its settings in Yoruba region of Nigeria and Cotonou, a francophone domain of Republic of Benin, a francophone setting. Data were gathered from dialogues in Part 1 and 2 of Abeni. Results show deployment of switching and mixing of Yoruba and French codes by the characters in the movie. Also, the study added the concepts of code-conflicting and gesticulation as solutions to conflict, switching and mixing of codes.